INTERNATIONAL CRIMINAL COURT – YOUNG BUT IMPORTANT PART OF INTERNATIONAL JUSTICE - Petar Stanojević; Zoran Pavlović; Snežana Prelević (Pravo, 2009)
The idea of the establishment of international criminal court as a means of solving international disputes originating from the nineteenth century. „Leipzig processes“ conducted during 1919. year against former members of the German Army and Navy have shown that the national courts cannot expect sufficient impartiality in regard to war crimes. In Nuremberg, was through the tendency to individual procedures and to not be turn in the trial all the German people, promoted the principle of individual criminal responsibility. International Criminal Tribunal for the Former Yugoslavia and Rwanda were promoted through decisions of the Security Council from 1993. and 1994. year. The existence of a legal basis and powers of the Security Council to form an ad hoc tribunals is the subject of numerous debates. At the diplomatic conference held in Rome, under the auspices of the United Nations, was adopted the Statute of the permanent International Criminal Court. Opening ceremony was followed on the 11. of March 2003. In taking an oath by the judges. The fact that a permanent International Criminal Court is a young body indicates how difficulties were in the building of such institutions, and that the overall work in the field of law is only in a processes, mostly on the development of mechanisms which would take away defects that are observed in similar trials that history abounds.